2010
DOI: 10.1590/s1984-70332010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and genetic diversity of potato cultivars using SSR and RAPD markers

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
(26 reference statements)
4
18
0
3
Order By: Relevance
“…The cophenetic correlation coefficient of the dendrogram (Figure 1), was 0.69, below the 0.80 considered by Sokal and Rohlf (1962) as indicative of a good adjustment between the original distance matrix and the graphic distance, therefore there may be some incongruities in the grouping of the 28 accessions, that could also been affected by sample size. Incongruities in clustering have also been reported by other authors such as Santos et al (2010) in Allium cepa, Vieira et al (2005) in Zea mays and Rocha et al (2010) in potato cultivars. Using the average similarity of 0.44 as cutting point, nine groups were formed: group 1 (accessions 1, 9, 10), group 2 (accessions Figure 1 -Dendrogram of genetic similarity based on Jaccard Coefficient for 28 accessions of T. riograndense using SSR markers.…”
Section: Resultssupporting
confidence: 76%
“…The cophenetic correlation coefficient of the dendrogram (Figure 1), was 0.69, below the 0.80 considered by Sokal and Rohlf (1962) as indicative of a good adjustment between the original distance matrix and the graphic distance, therefore there may be some incongruities in the grouping of the 28 accessions, that could also been affected by sample size. Incongruities in clustering have also been reported by other authors such as Santos et al (2010) in Allium cepa, Vieira et al (2005) in Zea mays and Rocha et al (2010) in potato cultivars. Using the average similarity of 0.44 as cutting point, nine groups were formed: group 1 (accessions 1, 9, 10), group 2 (accessions Figure 1 -Dendrogram of genetic similarity based on Jaccard Coefficient for 28 accessions of T. riograndense using SSR markers.…”
Section: Resultssupporting
confidence: 76%
“…Previous studies of genetic diversity using PCR based molecular markers reported similar results. Rocha et al (2010) and Ghislain et al (2006), observed low correlation between RAPD and SSR. Similarly, Milbourne et al (1997), obtained low correlation between RAPD, AFLP and SSR.…”
Section: Discussionmentioning
confidence: 93%
“…Cultivar identification and genetic relationships using RAPD markers in potato is well documented (Mori et al, 1993;Charchravarty et al, 2003;Orona-Castro et al, 2006;Yasmin et al, 2006 andRocha et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Compared to other molecular markers, RAPD is easy to be conducted, fast, requiring a small amount of DNA (0.5 -50 ng), does not require radioisotopes and does not require prior information of DNA sequence of the sample [9,10]. This technique has been widely used to analyze genetic diversity in crops such as citrus, sugarcane, durian sukun, grape, potato, soybean, kenaf, warty cabbage and cotton [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%